Examines several things that affect the price of banking stocks: Evidence from Indonesia - Ameliana, Yana (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study analyzes the effect of return on assets (ROA), net profit margin (NPM), debt-to-equity ratio (DER), and earnings per share (EPS) on the share price of banking companies on the Indonesia Stock Exchange (IDX). Research Design and Methodology: This study uses secondary data from 6 banking companies selected by purposive sampling based on financial reports for 2018–2022. The analysis was conducted using IBM SPSS version 25 to test the relationship between these variables. Findings and Discussion: The analysis shows that EPS has a positive and significant effect on stock prices, while DER shows a negative but insignificant effect. ROA and NPM show a positive but insignificant effect. Implications: This research guides investors to pay more attention to EPS when making investment decisions and encourages companies to improve operational performance to attract investors.